ProTaper Universal Manual Technique in Premolar with Two Roots and Three Root Canals (International Journal of Medical and Surgical Sciences, 2015)
The high morphological complexity of premolars, has led to propose different techniques for successful endodontic therapy. The purpose of this report is to describe the ProTaper manual technique in a second mandibular premolar showing a high anatomical complexity. A patient of 19 years old co- mes to the clinic of endodontic in the Regional Hospi- tal (Temuco), diagnosed with irreversible pulpitis on tooth 35. Radiographic examination found that the tooth has two roots. For clinical suspicion of the presence of a third canal a Cone Beam computed tomography was requested, which confirmed the existence of a distolingual canal. Because it is a complex case, the increased taper endodontic technique was performed, allowing us to complete the endodontic therapy in less time and with less difficulty.
Keywords: Premolars; Tooth roots; Root canals